2023
DOI: 10.3390/ijms241210273
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Plasma Cannabidiol Concentrations in Women and Men: A Randomized, Placebo-Controlled, Crossover Study

Abstract: The potential therapeutic benefits of cannabidiol (CBD) require further study. Here, we report a triple-blind (participant, investigator, and outcome assessor) placebo-controlled crossover study in which 62 hypertensive volunteers were randomly assigned to receive the recently developed DehydraTECH2.0 CBD formulation or a placebo. This is the first study to have been conducted using the DehydraTECH2.0 CBD formulation over a 12-week study duration. The new formulation’s long-term effects on CBD concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Further, FAAH expression levels in the cerebellum were higher for Tat(+) males compared to Tat(+) females and also compared to Tat(−) males, which supports the finding of Tat(+) males displaying high AA levels in the cerebellum, potentially due to increased breakdown of AEA, which however demonstrated no differences in AEA expression based on sex or Tat expression in our study. More research is needed to understand how sex alters the endocannabinoid system in PLWH and how it relates to neuroinflammation and HAND, but vulnerabilities to HAND symptoms ( Levine et al, 2021 ; Arkell et al, 2022 ; Yuan et al, 2022 ; Batinic et al, 2023 ; MacNair et al, 2023 ) and immune activation ( Funderburg and Mehta, 2016 ; Koethe et al, 2020 ) have been reported to be higher in women compared to men. Whereas a recent study did not find sex differences in various metabolites of the AA cascade of gp120 transgenic mice, transcriptomic analysis revealed sexual dimorphism of AA pathway-related genes, and females appear to be more responsive to the lipoxygenase pathway compared to males ( Koethe, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, FAAH expression levels in the cerebellum were higher for Tat(+) males compared to Tat(+) females and also compared to Tat(−) males, which supports the finding of Tat(+) males displaying high AA levels in the cerebellum, potentially due to increased breakdown of AEA, which however demonstrated no differences in AEA expression based on sex or Tat expression in our study. More research is needed to understand how sex alters the endocannabinoid system in PLWH and how it relates to neuroinflammation and HAND, but vulnerabilities to HAND symptoms ( Levine et al, 2021 ; Arkell et al, 2022 ; Yuan et al, 2022 ; Batinic et al, 2023 ; MacNair et al, 2023 ) and immune activation ( Funderburg and Mehta, 2016 ; Koethe et al, 2020 ) have been reported to be higher in women compared to men. Whereas a recent study did not find sex differences in various metabolites of the AA cascade of gp120 transgenic mice, transcriptomic analysis revealed sexual dimorphism of AA pathway-related genes, and females appear to be more responsive to the lipoxygenase pathway compared to males ( Koethe, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent clinical studies that either administered CBD for 7 days or cannabis acutely did not find concentration differences for CBD and/or CBD-7-COOH in plasma of healthy individuals [160,161]. However, the 7-day oral CBD administration study showed higher accumulation of CBD metabolites in plasma of females over time, which also is supported in a 12week clinical CBD study [162], suggesting sex differences in CBD metabolism or elimination [161]. In contrast, not much is known about how cannabidiol is metabolized in PLWH or neuroHIV mouse models.…”
Section: Discussionmentioning
confidence: 68%
“…An increasing body of evidence-based information available, including multiple CBD human research, now supports the long-standing use of cannabis and CBD products to treat a variety of medical conditions: symptoms of chronic pain, inflammation, cardiovascular disease, mental health issues, spasticity associated with multiple sclerosis and malignancies without serious side effects [ 17 , 18 ]. With the development of novel CBD formulations, smaller doses may lead to increased absorption and, consequently, greater health benefits [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%